Perfil nutricional e bioativo de subprodutos do processamento de acerola e goiaba fermentados espontaneamente e suas farinhas - Oliveira, Sabrina Duarte de (2024)
With this research, we investigated the spontaneous fermentation of by-products from the processing of acerola (Malpighia emarginata D.C., ACE) and guava (Psidium guajava L., GUA) at a temperature of 37 °C, at 200 rpm, for 120 hours, evaluating changes in the profile of bioactive compounds during fermentation. Furthermore, we prepare a flour from these by-products fermented for 48 hours under the conditions already mentioned. Before fermentation, physical-chemical characterization analyses of the acerola and guava by-products in natura were carried out. At intervals of zero, 8, 24, 48, 72 and 120 hours of fermentation, viable cell counts were performed. The physicochemical parameters, content of bioactive compounds (phenolic profile and total phenolics, total carotenoids, flavonoids and vitamin C) and antioxidant activity (FRAP and ABTS) were evaluated at times zero, 48 and 120 hours of fermentation. Flours from acerola and guava byproducts fermented for 48 hours (ACES and GUAS, respectively), as well in natura acerola and guava flours (ACE and GUA, respectively) were evaluated for their physicochemical characteristics, dietary fiber, profile of bioactive compounds (phenolic compounds, sugars and organic acids) and elemental composition. There was a significant increase (p≤0.05) in the viable cell count in ACE and GUA in 24 h of fermentation, with the highest viable cell counts (p≤0.05) being observed after 24 h for GUA (8 .9 log CFU/mL) and after 48 h for ACE. There was a decrease in the content of total soluble solids, an increase in titratable acidity and lactic acid content, and a reduction in pH, for fermented by-products, as well as for ACES and GUAS (p≤0.05). Regarding the colorimetry parameters of the fermented by-products, there was an increase in luminosity and a reduction in contrast throughout fermentation, and the treatments presented a tone tending to go from red to yellowish-red during this period (p≤0.05), while for flours, ACES had an increase in brightness, while GUAS had an increase in contrast. The ascorbic acid content was higher at zero fermentation time for ACE; however, this value reduced during fermentation (p≤0.05), for GUA, the ascorbic acid content increased with fermentation (p≤0.05). Fermentation contributed to an increase in the content of flavonoids and total phenolics in the fermented by-products, which possibly favored the greater antioxidant activity observed at all times of fermentation, especially for ACE. The insoluble fiber content was higher than the soluble fiber content in fermented flours. Potassium was the predominant mineral found in all flours, followed by magnesium and manganese, the iron and zinc content increased after fermentation. The concentrations of fructose and glucose decreased in fermented flours at the same time as there was an increase in organic acids. Gallic acid was the phenolic compound found in greatest quantity in acerola flour and hesperidin was the flavone found in greatest quantity in guava flour. The results indicate that the natural fermentation of by-products from the processing of acerola and guava, as well as the flour obtained from these fermented by-products, favors an increase in the content of bioactive compounds and antioxidant activity, indicating that this process is an alternative to add multifunctionality to by-products fruit, in addition to its potential to promote health and bring benefits to the environment.